(6-x)(6+x)-(x-11)x=18

Simple and best practice solution for (6-x)(6+x)-(x-11)x=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6-x)(6+x)-(x-11)x=18 equation:


Simplifying
(6 + -1x)(6 + x) + -1(x + -11) * x = 18

Multiply (6 + -1x) * (6 + x)
(6(6 + x) + -1x * (6 + x)) + -1(x + -11) * x = 18
((6 * 6 + x * 6) + -1x * (6 + x)) + -1(x + -11) * x = 18
((36 + 6x) + -1x * (6 + x)) + -1(x + -11) * x = 18
(36 + 6x + (6 * -1x + x * -1x)) + -1(x + -11) * x = 18
(36 + 6x + (-6x + -1x2)) + -1(x + -11) * x = 18

Combine like terms: 6x + -6x = 0
(36 + 0 + -1x2) + -1(x + -11) * x = 18
(36 + -1x2) + -1(x + -11) * x = 18

Reorder the terms:
36 + -1x2 + -1(-11 + x) * x = 18

Reorder the terms for easier multiplication:
36 + -1x2 + -1x(-11 + x) = 18
36 + -1x2 + (-11 * -1x + x * -1x) = 18
36 + -1x2 + (11x + -1x2) = 18

Reorder the terms:
36 + 11x + -1x2 + -1x2 = 18

Combine like terms: -1x2 + -1x2 = -2x2
36 + 11x + -2x2 = 18

Solving
36 + 11x + -2x2 = 18

Solving for variable 'x'.

Reorder the terms:
36 + -18 + 11x + -2x2 = 18 + -18

Combine like terms: 36 + -18 = 18
18 + 11x + -2x2 = 18 + -18

Combine like terms: 18 + -18 = 0
18 + 11x + -2x2 = 0

Begin completing the square.  Divide all terms by
-2 the coefficient of the squared term: 

Divide each side by '-2'.
-9 + -5.5x + x2 = 0

Move the constant term to the right:

Add '9' to each side of the equation.
-9 + -5.5x + 9 + x2 = 0 + 9

Reorder the terms:
-9 + 9 + -5.5x + x2 = 0 + 9

Combine like terms: -9 + 9 = 0
0 + -5.5x + x2 = 0 + 9
-5.5x + x2 = 0 + 9

Combine like terms: 0 + 9 = 9
-5.5x + x2 = 9

The x term is -5.5x.  Take half its coefficient (-2.75).
Square it (7.5625) and add it to both sides.

Add '7.5625' to each side of the equation.
-5.5x + 7.5625 + x2 = 9 + 7.5625

Reorder the terms:
7.5625 + -5.5x + x2 = 9 + 7.5625

Combine like terms: 9 + 7.5625 = 16.5625
7.5625 + -5.5x + x2 = 16.5625

Factor a perfect square on the left side:
(x + -2.75)(x + -2.75) = 16.5625

Calculate the square root of the right side: 4.069705149

Break this problem into two subproblems by setting 
(x + -2.75) equal to 4.069705149 and -4.069705149.

Subproblem 1

x + -2.75 = 4.069705149 Simplifying x + -2.75 = 4.069705149 Reorder the terms: -2.75 + x = 4.069705149 Solving -2.75 + x = 4.069705149 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.75' to each side of the equation. -2.75 + 2.75 + x = 4.069705149 + 2.75 Combine like terms: -2.75 + 2.75 = 0.00 0.00 + x = 4.069705149 + 2.75 x = 4.069705149 + 2.75 Combine like terms: 4.069705149 + 2.75 = 6.819705149 x = 6.819705149 Simplifying x = 6.819705149

Subproblem 2

x + -2.75 = -4.069705149 Simplifying x + -2.75 = -4.069705149 Reorder the terms: -2.75 + x = -4.069705149 Solving -2.75 + x = -4.069705149 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.75' to each side of the equation. -2.75 + 2.75 + x = -4.069705149 + 2.75 Combine like terms: -2.75 + 2.75 = 0.00 0.00 + x = -4.069705149 + 2.75 x = -4.069705149 + 2.75 Combine like terms: -4.069705149 + 2.75 = -1.319705149 x = -1.319705149 Simplifying x = -1.319705149

Solution

The solution to the problem is based on the solutions from the subproblems. x = {6.819705149, -1.319705149}

See similar equations:

| x+(-1/2)=4 | | x=4.2+-0.5y | | 10x+5y=42 | | 5y=3x+2forx | | 4.00/5.00x=20 | | x^2+17.4*x-17.4=0 | | (x+3/2)+(3/4)=(3x/2)-1 | | x^2/(2-2x)-8.7=0 | | x^2/(2-2x)=8.7 | | (6x/8)+(4x/2)-5=(3x/4) | | 187+15/100 | | 3x^2-3y=0 | | (5/12)-(1/3x)=(2/3x)-(7/6) | | (3x/2)+(1/2)=(4x/5)+(3/5) | | 3xy-6x=0 | | (4x/6)+(x/5)=(2/3)-(x/5) | | 41/2+11/6=4 | | 183-7x=29x+19 | | 2x+132=7x-13 | | 5*(5*3-25)+4= | | 6x+35=15x-17 | | 5x+12y=60 | | 5/3k=10 | | -44=9p-8 | | -5x-4=66 | | j-3=-14 | | 2s+3t=13 | | (x+7)x+12=0 | | ax+5=6x+b | | A=24-(10-(20-a)) | | A=24-(10-(20-a)) | | 5(2x-3)=-105 |

Equations solver categories